Influences on clinical practice: the case of glue ear. Issue 2 (1st June 1999) - Dopson, S; Miller, R; Dawson, S; Sutherland, K
Abstract : A case study of clinical practice in children with glue ear is presented. The case is part of a larger project, funded by the North Thames Research and Development Programme, that sought to explore the part played by clinicians in the implementation of research and development into practice in two areas: adult asthma and glue ear in children. What is striking about this case is the differences found in every area of the analysis. That is, diversity was found in views about diagnosis and treatment of glue ear; the organisation of related services; and in the reported practice of our interviewees, both between particular groupings of clinical staff and within these groupings. The challenge inherent in the case is to go beyond describing the complexity and differences that were found, and look for patterns in the accounts of practice and tease out why such patterns may occur.